2012
DOI: 10.1371/journal.pone.0028737
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Derivatives from Rubus ulmifolius Inhibit Staphylococcus aureus Biofilm Formation and Improve Response to Antibiotics

Abstract: BackgroundBiofilms contribute to the pathogenesis of many forms of Staphylococcus aureus infection. Treatment of these infections is complicated by intrinsic resistance to conventional antibiotics, thus creating an urgent need for strategies that can be used for the prevention and treatment of biofilm-associated infections.Methodology/Principal FindingsThis study demonstrates that a botanical natural product composition (220D-F2) rich in ellagic acid and its derivatives can limit S. aureus biofilm formation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
143
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 53 publications
2
143
0
1
Order By: Relevance
“…The reduction in biofilm attachment in a challenging polymicrobial in vivo model confirms the in vitro results and is consistent with release of active concentrations of antibiotic from various drug delivery vehicles [22,45,51,54,63]. Scanning electron microscopy images of biofilm formation on implants resembled images from similar retrieved infected implants [10,52] with rounded S aureus and rod-shaped P aeruginosa colonies visible in untreated groups.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The reduction in biofilm attachment in a challenging polymicrobial in vivo model confirms the in vitro results and is consistent with release of active concentrations of antibiotic from various drug delivery vehicles [22,45,51,54,63]. Scanning electron microscopy images of biofilm formation on implants resembled images from similar retrieved infected implants [10,52] with rounded S aureus and rod-shaped P aeruginosa colonies visible in untreated groups.…”
Section: Discussionsupporting
confidence: 81%
“…The limitations of the animal model include the small size, soft tissue instead of orthopaedic implantation, and limited diffusion of physiologic substances within the sequestrum of the catheter. The animal model is useful as a screening tool for antibiofilm activity in vivo [54,74,75], where the catheter serves as a sequestrum for localizing the bacterial inoculum and as a nidus for biofilm formation. Because of difficulty in applying coatings directly to the catheter, we modified the catheter-associated biofilm model by including an easily coated stainless steel wire.…”
Section: Discussionmentioning
confidence: 99%
“…Pentagalloyl glucose (one of the major components of commercial tannic acid) and ellagic acid (another plant-derived polyphenolic compound) have also been shown to inhibit biofilm formation in S. aureus (46,47). To the best of our knowledge, no genetic mechanism for the antibiofilm properties of tannic acid or related polyphenols in S. aureus has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…11 It was reported that bacteria within a biofilm can reach a much higher cell density (10 11 CFU mL À1 ) than do planktonic bacteria (10 8 CFU mL À1 ). 27 A number of the quorum-sensing signals involved in biofilm formation have already been identified but many of them remain unidentified. In addition, biofilm development needs the activation and suppression of a wide array of genes.…”
Section: Bacterial Interfacesmentioning
confidence: 99%